2019
DOI: 10.1007/s10798-019-09528-2
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering early indicators of fixation during the concept development stage of children’s design processes

Abstract: In this paper, we explore the early indicators of design fixation occurring during the concept development stage of children's design processes. This type of fixation, which we named: concept fixation, causes a blind adherence to the current (possibly unfavourable) state of a design idea. Its occurrence hampers the creative thinking processes present in a design process, which in turn stagnates the development of initial design ideas into final designs. Until now, research on design fixation has mainly focusse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 43 publications
0
23
0
Order By: Relevance
“…Although favouring convergent feedback is an understandable strategy when wanting to eliminate ambiguity and encourage reflection and evaluation, these results show that students' convergent thinking processes are not always that easily triggered. At a primary school level, Schut et al (2019b) also observed that the high level of convergent design feedback did not always promote constructive dialogue. Similar to the studies at a university level, it was observed that the convergent feedback did not automatically trigger reflection and evaluation with the young novice designers.…”
Section: Non-constructive Feedback Dialoguesmentioning
confidence: 98%
See 4 more Smart Citations
“…Although favouring convergent feedback is an understandable strategy when wanting to eliminate ambiguity and encourage reflection and evaluation, these results show that students' convergent thinking processes are not always that easily triggered. At a primary school level, Schut et al (2019b) also observed that the high level of convergent design feedback did not always promote constructive dialogue. Similar to the studies at a university level, it was observed that the convergent feedback did not automatically trigger reflection and evaluation with the young novice designers.…”
Section: Non-constructive Feedback Dialoguesmentioning
confidence: 98%
“…Thus far, little is known about design feedback in the context of primary education (Schut et al 2019b). However, feedback interventions are a common educational practice within the context of design disciplines at a university level and are known as design critiques (crits) or design reviews (Anthony 1991;Healy 2016).…”
Section: Feedback In Design Educationmentioning
confidence: 99%
See 3 more Smart Citations